Inverse Functions
Jump to navigation
Jump to search
This article is part of the MathHelp Tutoring Wiki |
If f^{-1} is the inverse of function f then (f^{-1} o f)=x or f^{-1}(f(x))=x.
Example: Prove g(x)=5/(x-1) is an inverse of f(x)=1+(5/x)
f(g(x))=1+(5/(5/(x-1)))
f(g(x))=1+(x-1)
f(g(x))=1+x-1=x
Example: Find the inverse function of f given by the following,
f(x) = (x-3)^{2} for x>=3 (this has to hold so that the inverse function does exist)
The function is written in the following format,
y = (x - 3)^{2}
As a result, there are two possible solutions given below:
x - 3 = sqrt(y) or x - 3 = - sqrt(y)
However since sqrt(y) is always larger than zero and x >= 3, the first solution is chosen,
x - 3 = sqrt(y), therefore, x = sqrt(y) + 3;
f^{-1} (y) = sqrt(y) + 3 or f^{-1}(x) = sqrt(x) + 3;
- Back to Differential Calculus
- Back to MathHelp